DETERMINANTS OF FINANCIAL REPORTING FRAUD IN INDONESIAN FINANCIAL SECTOR: A FRAUD HEXAGON PERSPECTIVE - Fatiha, Aulia Salwa; Laily, Nujmatul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study was conducted to identify and analyze several factors that contribute to financial reporting fraud by applying the Fraud Hexagon Theory perspective. The influence of the independent variables on the dependent variable is explained through an explanatory quantitative approach. The research sample includes companies listed in the financial sector on the IDX from 2019 to 2023 and was determined through a purposive sampling technique. The research data processing was analyzed using the logistic regression method. The findings indicate that the financial target variable, proxied as a pressure factor, has a positive influence on financial reporting fraud. Then the audit fees variable, proxied as a collusion factor, shows a negative influence on financial reporting fraud. While the CEO education variable proxied as a capability factor, the percentage of independent audit committee variable proxied as an opportunity factor, the external auditor switching variable proxied as a rationalization factor, and the family firm variable proxied as an ego factor, have no impact on financial reporting fraud. This study offers theoretical implications for the development of literature on financial reporting fraud based on the Fraud Hexagon Theory, and provides practical implications for all stakeholders to prevent factors that can trigger financial reporting fraud.